The dynamics of training programs for the unemployed - Aderonke Osikominu (IZA World of Labor, 2021)
Time plays an important role in both the design and interpretation of evaluation studies of training programs. While the start and duration of a training program are closely linked to the evolution of job opportunities, the impact of training programs in the short and longer term changes over time. Neglecting these "dynamics" could lead to an unduly negative assessment of the effects of certain training schemes. Therefore, a better understanding of the dynamic relationship between different types of training and their respective labor market outcomes is essential for a better design and interpretation of evaluation studies.
Keywords: J64; M53; 330; active labor market policy; job training; dynamic effects